Estrutura e atividade da proteína 2-hidroximuconato semialdeído desidrogenase (NahI) de Pseudomonas putida G7, uma enzima da via de degradação do naftaleno - Simara Semíramis de Araújo (2015)
The Polycyclic Aromatic Hydrocarbons (PAHs), a group of organic compounds consisting of fused benzene rings, are contaminants widely distributed in the environment due to natural as well as anthropogenic sources. Activities of production of coal, refining and transportation of oil are the major contributors to the contamination with PAHs. Due to their ubiquitous occurrence, potential to bio-accumulate and carcinogenic activity, a number of PAHs were listed as priority pollutants for remediation highlighting the importance of their removal from the environment. Several microorganisms have been extensively studied because of its versatility to degrade a wide range of aromatic compounds. The bacterium Pseudomonas putida G7 has a plasmid associated with the metabolism of naphthalene, the simplest and most abundant PAH. Its degradation by P. putida occurs through the upper and the lower catabolic pathways. NahI, a 2-hydroxymuconate semialdehyde dehydrogenase (2-HMSD) belonging to the lower pathway, converts 2-hydroxymuconate semialdehyde (2-HMS) to 2- hydroxymuconate (2-HM) in the presence of NAD+. A common feature among aldehyde dehydrogenases (ALDHs) is the similar scaffold, even despite their overall low sequence identity, modes of oligomerization and substrate specificity. Thus, this study was proposed to characterize the structure and kinetics of NahI. By elucidation of its three-dimensional structure and comparison with other ALDHS, it becomes possible to infer distinctions in the catalytic site that are responsible for systematic changes in the kinetic properties of these enzymes within a variety of aldehyde substrates After purification by affinity and sizeexclusion chromatography, dynamic light scattering (DLS) and small-angle X-ray scattering (SAXS) experiments were conducted to analyze the oligomeric state of the enzyme in solution, which was identified as being a tetramer. With regard to the crystal structure, NahI displayed a typical / aldehyde dehydrogenase superfamily fold with three well defined domains: the oligomerization domain, the nucleotide binding and the catalytic domains. Through crystallographic symmetry operations, the NahI tetramer formed by a dimer of dimers was observed. Kinetic assays confirmed the preference of the enzyme for the aliphatic substrate 2-HMS. On the other hand, NahI showed no activity with salicylaldehyde, the natural substrate for NahF enzyme, another ALDH belonging to the same naphthalenedegradation pathway. Mutations have been proposed for NahI in order to increase the volume of the catalytic pocket, since bulky side chain residues could hinder the activity of this enzyme with aromatic substrates. Surprisingly, the mutant forms showed no activity with salicylaldehyde. Moreover, the enlargement of the catalytic pocket entrance slightly affected the affinity of the enzyme for its natural substrate, 2-HMS. It also suggests that the L156 residue appears to be crucial for the oxidation of the substrate. For the first time, these findings show the structural and kinetic properties relative to the NahI enzyme and highlights further studies concerning the identity and function of critical residues for catalysis and description of how the reaction proceeds.